PENGARUH MINAT BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR SISWA KELAS V SD DI KOTA BAUBAU - Naya; Alfianita Endang Syah, Rani; Keliobas, Miska; Sarnia; Hermansyah, Fikram; Anugra Jaya, Fadli; Rahmalia Natsir , Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the influence of mathematics learning interest on the mathematics learning outcomes of fifth-grade elementary school students in Baubau City, involving four schools: SDN 2 Nganganaumala, SDN 1 Bonebone, SDN 3 Katobengke, and SDN 1 Kaobula. Preliminary observations revealed varying levels of student enthusiasm during mathematics lessons, which was suspected to impact their learning outcomes. The study employed a quantitative ex-post facto correlational method, utilizing a saturated sampling technique with 79 fifth-grade students as respondents. Data were collected via a learning interest questionnaire and mathematics midterm exam scores, then analyzed using Pearson Product Moment correlation, a significance test (t-test), and simple linear regression. The results showed an average learning interest score of 63.38 (low category) across the four schools, while the average learning outcome score was 72.52. Correlation analysis yielded an r-calculated value of 0.385 and a t-calculated value of 3.656—exceeding the t-table value of 1.991 at a 5% significance level—indicating a positive and significant relationship, albeit within the low category. The coefficient of determination was 14.79%, indicating that learning interest contributed 14.79% to learning outcomes, while the remaining 85.21% was influenced by other factors. These findings confirm that mathematics learning interest has a positive and significant effect on learning outcomes; however, teachers and schools must still consider other factors to optimize students' mathematics learning achievements.